Contextual Teaching and Learning–Based Discovery Learning to Improve Students’ Learning Outcomes in Earth’s Structure and Geological Processes - Asih Kasan; Salma Samputri; Yenni Rahman (SEARCH: Science Education Research Journal, 2026)
The low final science learning outcomes of Grade VIII students in earth science became the initial problem of this study. This classroom action research aimed to describe the improvement trends of students’ final learning outcomes through Contextual Teaching and Learning-Based Discovery Learning oriented toward deep learning on Earth’s Structure and Geological Processes. The study involved 36 students of class VIII.2 and was conducted through a pre-cycle stage and two action cycles consisting of planning, action, observation, and reflection. Cycle I focused on earth structure and plate tectonics, while Cycle II focused on volcanoes and earthquakes. The pre-cycle scores were obtained from a different science topic and were used only as baseline data, not as a pretest on the same topic. Data were collected from student worksheets, daily quizzes, final cycle tests, documentation, and researcher reflection notes. The data were analyzed using descriptive statistics, learning outcome categories, N-gain, and standardized mean difference as descriptive measures of change. The mean final score increased from 46.81 in the pre-cycle to 64.77 in Cycle I and 73.58 in Cycle II. The proportion of students in the low category decreased from 83.33% to 25.00%, while the high category increased from 5.56% to 47.22%. The overall N-gain was 0.50, and the standardized mean difference was 1.67, indicating a meaningful descriptive change during the action process. Reflection results showed that clearer group roles, stronger visual and concrete representations, and the use of local and national geological contexts supported more active participation and better conceptual connection. These findings suggest that Contextual Teaching and Learning-Based Discovery Learning was associated with positive trends in students’ final learning outcomes and supported more meaningful learning of abstract earth science concepts within the limitations of classroom action research.